Aspek Hukum Penagihan dalam Layanan Fintech Peer-To-Peer Lending: Tinjauan terhadap Prinsip Perlindungan Konsumen - Elin Maysa Arlin; Joanita Jalianery; Evi Evi; Fransisco Fransisco (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the collection mechanism regulations in Fintech Peerto-Peer Lending services based on Financial Services Authority Regulation Number 40 of 2024 and Financial Services Authority Circular Letter Number 19/SEOJK.06/2025 from the perspective of consumer protection and civil law. This research is a normative legal study with a statutory and conceptual approach. The results indicate that POJK 40/2024 provides a normative basis for collection implementation, but does not explicitly regulate operational standards regarding ethics, frequency and collection limits, resulting in unclear norms. Meanwhile, SEOJK 19/SEOJK.06/2025 regulates restrictions on device access and the use of emergency contacts, but the phrase